Guanine nucleotide exchange factors and colon neoplasia - Njei, Lea-Pearl; Sampaio Moura, Natalia; Schledwitz, Alyssa; Griffiths, Kelly; Cheng, Kunrong; Raufman, Jean-Pierre (Frontiers in Cell and Developmental Biology, 2024)
Despite many diagnostic and therapeutic advances, colorectal cancer (CRC) remains the second leading cause of cancer death for men and women in the United States. Alarmingly, for reasons currently unknown, the demographics of this disease have shifted towards a younger population. Hence, understanding the molecular mechanisms underlying CRC initiation and progression and leveraging these findings for therapeutic purposes remains a priority. Here, we review critically the evidence that canonical and noncanonical actions of guanine nucleotide exchange factors (GEFs) play important roles in CRC evolution. Rho GEF GTPases, which switch between inactive GDPbound and active GTP-bound states, are commonly overexpressed and activated in a variety of cancers, including CRC, and may be tractable therapeutic targets. In addition to comprehensively reviewing this field, we focus on Rho/Rac GEFs that are involved in regulating key functions of normal and neoplastic cells like cell polarity, vesicle trafficking, cell cycle regulation, and transcriptional dynamics. Prime examples of such Rho/Rac GEFs include βPak-interacting exchange factor (βPix), a Rho family GEF for Cdc42/Rac1, Tiam1, GEF-H1, RGNEF, and other GEFs implicated in CRC development and progression. Throughout this analysis, we explore how these findings fill key gaps in knowledge regarding the molecular basis of colon carcinogenesis and how they may be leveraged to treat advanced CRC. Lastly, we address potential future directions for research into the role of GEFs as CRC biomarkers and therapeutic targets. In this regard, leveraging the noncanonical actions of GEFs appears to provide a relatively unexplored opportunity requiring further investigation.